"We are in this together:" dyadic-level influence and decision-making among HIV serodiscordant couples in Tanzania receiving access to PrEP - Virginia A. Fonner; Jacob Ntogwisangu; Isihaka Hamidu; Juliet Joseph; Joshua Fields; Evans Evans; Jordan Kilewo; Claire Bailey; Lloyd Goldsamt; Celia B. Fisher; Kevin R. O'Reilly; Theonest Ruta; et al. (BMC, 2021)
Abstract Background A substantial number of new HIV infections in sub-Saharan Africa occur within stable couples. Biomedical prevention (pre-exposure prophylaxis, PrEP) and treatment (antiretroviral therapy, ART) can provide benefits to sexual partners and can be used to prevent infection within HIV serodiscordant couples. However, research is typically focused on individuals, not dyads, even when the intervention may directly or indirectly impact sexual partners. Gaps remain in understanding best practices for recruitment, informed consent, and intervention implementation in studies involving HIV prevention and treatment among heterosexual serodiscordant couples. This qualitative study was undertaken to understand and describe decision-making and dyadic-level influence among members of serodiscordant couples regarding (1) participation in a dyadic-based research study involving HIV self-testing and access to PrEP, and (2) utilization of PrEP and ART. Methods This qualitative study was nested within an observational cohort study assessing the acceptability of home-based couples' HIV self-testing and uptake of dyadic care for serodiscordant couples involving facilitated referral for HIV-positive partners and access to PrEP for HIV-negative partners. Semi-structured in-depth interviews were conducted among a subset of study participants (n = 22) as well as individuals involved in serodiscordant relationships who chose not to participate (n = 9). Interviews focused on couples' decision-making regarding study participation and dyadic-level influence on medication use. Interviews were transcribed verbatim and translated from Kiswahili into English. Data were analyzed using thematic analysis. Results Three major themes were identified: (1) HIV as "two people's secret" and the elevated role of partner support in serodiscordant relationships; (2) the intersectional role of HIV-status and gender on decision-making; (3) the relational benefits of PrEP, including psychosocial benefits for the couple that extend beyond prevention. Conclusions The study found that couples made joint decisions regarding study participation and uptake of HIV-related medication. Relational autonomy and dyadic-level influence should be considered within research and programs involving HIV serodiscordant couples.